Pembinaan Praktik Fiqih Kewanitaan Dan Penggunaan Aplikasi Kalender Menstruasi Dalam Meningkatkan Kesehatan Reproduksi Remaja Putri Di Desa Karanghaur - Ana, Ana Yunitasari; Abdul Muis; Ainur Rofieq (JCSE: Journal of Community Service and Empowerment, 2023)
Fiqh study is indeed a very vital material. Because this is related to how Islamic law is carried out, which is related to mahdhah worship, therefore every Muslim woman must learn to understand it so that at the implementation level it can run well in accordance with religious orders. This service activity was carried out in the village of Karanghaur regarding the strengthening and mentoring of female fiqh and the application of the menstrual calendar application. In its implementation, it starts from the planning, implementation and evaluation stages which must be considered in preparing and implementing a program. The result of this activity is that the young women of Karanghaur village can understand female jurisprudence to maintain their reproductive health and assisted by the menstrual calendar application as a tool to remember their menstrual cycles, so that from the aspect of the Shari'a they can be implemented in everyday life. The participants showed enthusiasm by showing a positive attitude so that in this activity it was important to develop and follow up with discussion of other topics.